2012
DOI: 10.1093/imanum/drs022
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis for a coupled bulk-surface partial differential equation

Abstract: In this paper, we define a new finite-element method for numerically approximating the solution of a partial differential equation in a bulk region coupled to a surface partial differential equation posed on the boundary of the bulk domain. The key idea is to take a polyhedral approximation of the bulk region consisting of a union of simplices, and use piecewise polynomial boundary faces as an approximation of the surface. Two finite element spaces are defined, one in the bulk region and one on the surface, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
214
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(216 citation statements)
references
References 29 publications
2
214
0
Order By: Relevance
“…Here, C T is the constant of the trace inequality (12) and c G is the coercivity constant of the stability estimate (25). We conclude by choosing > 2C 2 T c 1 G , where the lower bound is independent of the mesh/boundary intersection, but not of the penalty parameter 1 in j. ; /.…”
Section: Enhancing Robustness: Ghost Penaltymentioning
confidence: 96%
See 1 more Smart Citation
“…Here, C T is the constant of the trace inequality (12) and c G is the coercivity constant of the stability estimate (25). We conclude by choosing > 2C 2 T c 1 G , where the lower bound is independent of the mesh/boundary intersection, but not of the penalty parameter 1 in j. ; /.…”
Section: Enhancing Robustness: Ghost Penaltymentioning
confidence: 96%
“…Applications are found, for example, in cell membrane transport; cf. [25]. Here, we no longer have a distinct side condition and can dispense with Nitsche's method.…”
Section: Other Interface Conditions Of Interestmentioning
confidence: 98%
“…See the appendix for details on how to compute radially symmetric solutions in this case. We remark that a priori error bounds for discretizations by fitted and unfitted finite element methods for related coupled linear bulk-surface elliptic partial differential equations have been obtained in [22,14,29].…”
Section: Comparison With Radially Symmetric Solutions In 2dmentioning
confidence: 98%
“…It must be observed that for the fractional-step θ method above, the computational mesh is continuously evolving according to the exponential growth and all matrices are assembled at different discretised surfaces depending on the time-level n. The number of degrees of freedom and the mesh connectivity remains constant throughout domain growth. For further details on the implementation of the evolving (bulk) surface finite element method we refer the interested reader to [2,6,7,23].…”
Section: Time Discretisationmentioning
confidence: 99%